Theoretical Foundations Of Formation Of VerbalLinguistic Competences - R.G. Rashidova (Zien Journals, 2024)
The article describes the theoretical foundations for the formation of speech and linguistic competencies in students, the content and essence of the concept of competence, and the opinions of academic researchers regarding the competency-based approach. The article also describes the types of competencies and the importance of competencies in teaching activities
Keywords: competence; sociolinguistic; communicative